Structure of the even-even (220-230) Th isotopes within the Framework IBM-2 - I.Atawiry, Mariam; M .El-kadi, Sadiq (Scientific Journal of University of Benghazi, 2025)
The specific In this study, some of the nuclear properties of the even-even thorium isotopes in the mass range A=(220–230) were studied within the interacting boson model (IBM-2) framework. The parameters in the Hamiltonian of the IBM-2 model were used to determine which one best fits the experimental spectrum. The NPBOS code was used to diagonalize this Hamiltonian, and the energy level was obtained. Our theoretical calculations and the latest experimental data showed a reasonable degree of agreement. From these calculations, it was possible to determine the dynamic symmetries of these isotopes based on several tests that rely in their calculations on energy levels. Based on the results of the tests used, The isotopes were classified as having rotational symmetry SU(3), had X(5) symmetry while the isotope had vibrational symmetry U(5), and the isotope had unstable gamma symmetry O(6). The phenomenon of backbending of these isotopes was studied, which only appeared in the isotope .